POPULATION ASSESSMENT OF THE TARICAYA (TESTUDINES: PODOCNEMIDIDAE: PODOCNEMIS UNIFILIS) IN THE TAHUAMANU RIVER, MADRE DE DIOS, PERU - FLORES-PONCE, Frank Christian (2022)
The taricaya, Podocnemis unifilis, is an aquatic turtle from the Amazon that hasbecome a flagship species at the national level and mainly in Madre de Dios. Despite this, it is subject to very high hunting pressure due to the use of its eggs for sale and self-consumption. In order to focus efforts that help its conservation, the population status of this species was studied in the Tahuamanu river, Madre de Dios. From July to September, by counting sunbathers, a total of 343 detections of 895 individuals were recorded, with a relative abundance of 1.11 ind./km traveled (SD = 0.65, SE = 0.15). In addition, a probability of beach use by the species of Ψ = 0.78 (SE = 0.06) was estimated (which represents 78% of occupation of the beaches of the Tahuamanu River), and additionally, its preference for large and sloping beaches. Finally, a total of 275 nests were recorded, being in the upper basin (near the Alto Purus National Park -PNAP) where the highest number of nests was observed. In conclusion, the taricaya uses the entire course of the Tahuamanu River, but the healthiest populations are found in the upper part, near the limits of the PNAP, and where management activities have contributed to the maintenance of P. unifilis populations.